Impact of dust accumulation on yield and yield components of soybean - Sharife HABIBPOUR; Majid AMINI DAHAGHI; Mohammad-Eghbal GHOBADI; Alaeddin KORDENAEEJ (Acta Agriculturae Slovenica)
This study aimed to characterize if dust sprayed on soybean foliage impacts its yield and yield component characteristics. In 2017 and 2018, soybean [Glycine max (L.) Merr.] was planted using a factorial randomized complete block design with three replicates. Plants were sprayed with a 20 g m-2 of dust at four stages of the growth cycle, including third-node, the beginning of flowering, the beginning of podding, and the beginning of seed formation. Dust spraying was then continued twice weekly until the late full seed stage. Plant measurements included yield, yield components, stomatal conductance, peroxidase, and superoxide dismutase antioxidant enzymes activities. Results showed that depending on the time of application, the dust coverage created a range of yield loss in soybeans, most likely due to a reduction in stomatal conductance, grains plant-1 and 100-seed mass. Therefore, soybean fields that are regularly exposed to dust might be subjected to reduced yield.